Unveiling the Voices of Cancer Survivors: A Narrative Study - Choudhri, Sadia (Italian Sociological Review, 2025)
Cancer profoundly disrupts an individual’s relations, outlook on life, and perceptions of who they are. Other than this, it also causes an identity crisis, triggering people to reunite their lives before the diagnosis with the transformations that illness has brought about. In this context, storytelling provides a key medium for comprehending, adaptability, and identity restoration. This study has been driven by the recognition that storytelling is vital in uniting the different accounts of cancer patients and survivors, leading them to regain meaning and value in their lives. This study makes use of Paul Ricoeur’s Narrative Identity theory (1992) to analyse 20 cancer survivor narratives from the Cancer Treatment Centres of America website. A web-based platform presents a space for survivors to voice their narratives and use language that probes endurance, transformation, and solidarity themes. Ricoeur’s principles of threefold mimesis (prefiguration, configuration, and refiguration) and the dialectic of sameness (idem) and selfhood (ipse) guide the analysis of how survivors linguistically frame their journey and recreate their identities from their experiences. Findings suggest that digital storytelling performs both as a therapeutic outlet and as a powerful tool for strengthening resilience. Survivors adopt stories to link their fractured experiences, reform their relationships, and regain their roles within their surroundings. The research underlines the transformative value of storytelling to promote emotional healing, fostering shared identities, and establishing solidarity within cancer care communities.